EXPECTANCY AND SALES PERSONNEL MOTIVATION TO CONTINUE WORK PERFORMANCE DURING THE COVID 19 PANDEMIC - Luh Devany; Maria Jacinta Arquisola (President University, 2021)
Declining level of public purchasing power affects several industries during the COVID- 19 pandemic. As one of the industries affected by the COVID-19, the decrease in sales performance felt by one of the telecommunication providers in Bali, Indonesia which has incurred loss in the first quarter of 2020. As a result, the sales personnel have experienced low level of motivation. The purpose of this study was to investigate howto motivate the sales personnel to continue work performance during the COVID-19 pandemic under the expectancy theory approach that consists of expectancy, instrumentality, and valence. The theory proposed if high level of efforts will lead to the attainment of high level of performances and high level of performances will be valued with desired outcomes in the future. Convenience sampling was used in this study. 110 respondents were collected and analyzed. The result shows simultaneous influences of independent variables toward dependent variable at p< .001 as the level of significance and the values of F= 69.493. This indicates that the sales personnel believe if theamount of effort given will be associated with the achievement of better performance and rewards. This study highlights the presence of expectancy variable which has a positive but not significant influence on motivation. This study suggests that expectancy variable should be increased while maintaining instrumentality and valence by setting realistic and achievable targets during the COVID-19 situation, providing necessary equipment and facilities to maximize skills and resources.Keywords: Expectancy, Instrumentality, Valence, Motivation, Sales personnel, Telecommunication, Indonesia